Application of PDCA cycle in improving qualified rate of standard processing for precision instruments (运用PDCA循环提高精密器械处理规范率的实践) - REN Xiajuan (任娟霞); WANG Yuena (王岳娜); LI Haiqing (李海青); SU Peirong (苏佩蓉); ZHU Kunkun (朱坤坤); JIA Tingting (贾婷婷) (中西医结合护理, 2022)
Objective To investigate the practice effect of PDCA cycle in improving the qualified rate of standard processing for precision instruments. Methods Totally 4870 pieces of precision instruments processed through a routine management procedure were included as the control group, another 4372 pieces of precision instruments processed through a PDCA cycle were included as the study group. The qualified rate of standard processing was calculated and compared between groups. Results The qualified rate of standard processing was 99. 02%(4329/4372) in the study group, which was higher than 91. 97%(4479/4870)in the control group(P＜0. 01). Conclusion The PDCA cycle is effective to improve the qualified rate of standard processing for precision instruments. It is of great significance for improving surgical nursing quality, ensuring patient safety, prolonging service life of instruments and making full use of medical resources. (目的 探讨运用PDCA循环提高精密器械处置规范率的效果。方法 选取2021年5月—6月消毒供应中心接收的4870件精密器械作为对照组, 采用常规管理流程进行处理; 选取2021年9月—10月接收的4372件精密器械作为试验组, 采用PDCA循环管理方法进行处理, 比较两组精密器械处理规范率。结果 试验组精密器械处理规范率为99. 02%(4329/4372), 对照组器械处置规范率为91. 97%(4479/4870), 差异有统计学意义(P＜0. 01)。结论 应用PDCA循环法能够有效提高精密器械的处理规范率, 对提高手术质量、保证患者安全、延长器械寿命、充分发挥医疗资源具有重要意义。)